Influence of selected bactericides on biofilm formation and viability of Xanthomonas citri subsp. citri. (December 2015) - Redondo, C.; Sena-Vélez, M.; Gell, I.; Ferragud, E.; Sabuquillo, P.; Graham, J.H.; Cubero, J.
Abstract: Citrus Bacterial Canker (CBC) is a serious disease that affects production of almost all commercial citrus cultivars in subtropical citrus growing regions worldwide. The causal agent, Xanthomonas citri subsp. citri ( Xcc ), is classified as a quarantine pathogen in European Union (EU) which necessitates treatment of citrus fruit before entry into the EU marketing zone. In this study, the effectiveness of selected bactericides for leaf and fruit disinfection was evaluated. Bacterial aggregation and viability were assayed on abiotic or biotic surfaces in vitro and in planta after treatments with NaCl, CuSO4, NaClO, sodium orthophenylphenate and two hydrogen peroxide based compounds. Most of the bactericides at higher concentrations reduced biofilm formation and Xcc viability compared to the non-treated control, but did not completely prevent or remove biofilms or eradicate Xcc from either biotic or abiotic surfaces. Some of the bactericides at sub-lethal concentrations increased aggregates in which Xcc was viable. Based on these results, we conclude that exposure to the bactericides is variable depending on biofilm formation and that plant and fruit disinfection will not only require treatment with an effective bactericide to kill the bacterium but also include the biofilm disruption. Highlights: We have evaluated the effect of different compounds on bacterial biofilms formed by Xanthomonas citri subsp. citri . Bactericides reduce biofilm formation at high concentration but are not able to completely prevent or remove biofilms. Some bactericides at low concentration induce bacterial aggregation and biofilm formation. Biofilm must be considered in strategies to control citrus bacterial canker.